THE ROLE OF CYBERHATE AS A COMPONENT OF CYBERBULLYING IN THE SYSTEM OF STAFF DEVELOPMENT IN PUBLIC SERVICE - Mykola Atanasov (Публічне управління та регіональний розвиток, 2025)
The article attempts to define the role of cyberhate as a component of cyberbullying. The introductory part emphasizes that the issue of cyberhate is a complex combination of misused, mediated and unregulated freedom of speech. Currently, debates continue in the world about its universal conceptualization. Meanwhile, cyberhate is defined as all forms of expression, mediated by information and communication technologies, inciting, justifying or promoting hatred or violence against individuals or groups based on their gender, race, ethnicity, religion, sexual orientation or other collective characteristics. The main part is devoted to a detailed analysis of the factors influencing the development of cyberhate and its further impact on public servants and staff. It is noted that for further better understanding and synthesis of certain factors, taking into account the results of the survey conducted by the author, the main factors are disclosed, namely: «Personal factors», «Cognitive factors», «Psychological factors» and «External factors». The classification of factors is based, in particular, on the nature of the factors, relevance, context of the factors that are the subject of consideration in scientific publications, and on the basis of consideration of the general definition of each specific factor. In conclusion, it is stated that since the emergence of the phenomenon of cyberbullying, interest in the issue of its manifestations and nature in various spheres and industries has recently increased. At the same time, it should be noted that its variety, namely cyberhate, unfortunately, has not yet received proper scientific analysis and assessment in the domestic scientific space. The survey conducted as part of our study showed a number of factors, including personal, psychological, cognitive, and external factors that influence the development of personnel in the public service and encourage public servants to commit actions that have signs of cyberbullying based on a review of scientific studies that are related to the questions themselves. In addition, all these factors were classified into negative and positive in order to thoroughly substantiate the influence of the studied factors on the manifestations of cyberhate and cyberbullying.